Всем нужна буква Ё, или заметки преподавателей русского языка как иностранного - Barbara Chlebda; Irena Danecka (Studia Rossica Posnaniensia)
Only a Russian native speaker who has adequate philological knowledge knows when the letter “Ё” should be used. According to an article presented on a website called GRAMOTA.Ru – a portal providing information about linguistic correctness, written by the website’s author, the use of the letter ‘Ё’ is obligatory only in certain cases. This leads to the conclusion that a learner of Russian should master all possible cases in which this letter is not used and know the relevant grammatical and historical justification. We, the teachers of Russian as a foreign language, believe that such an attitude is a sign of an incomprehensible disrespect for one’s own language as well as of a complete misunderstanding of substantial problems facing all students of the Russian language, which completely deserves to be called international.